Respuesta :
Answer:
D) [tex]x=2[/tex] and [tex]x=4[/tex]
Step-by-step explanation:
I assume the equation to be [tex]log_6(x^2+8)=1+log_6(x)[/tex]:
[tex]log_6(x^2+8)=1+log_6(x)[/tex]
[tex]log_6(x^2+8)-log_6(x)=1[/tex]
[tex]log_6(\frac{x^2+8}{x})=1[/tex]
[tex]\frac{x^2+8}{x}=6 [/tex]
[tex]x^2+8=6x[/tex]
[tex]x^2-6x+8=0[/tex]
[tex](x-2)(x-4)=0[/tex]
[tex]x=2[/tex] and [tex]x=4[/tex]
Both solutions indeed work because you can take the logarithm of a positive number, but not a negative number, unlike the rest of the answer choices.